BODY IMAGE (CITRA TUBUH) PEREMPUAN - Nur Azizah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Abstract: The development of the era and science become the reasons why somebody pays attention into his/her own body image. Every day people face a lot of media that expose body image, such as in advertising, a sitcom actress, a beauty model and beauty contest that many show their body image. The impressions that can create the perception of body image to people can be seen from the range of the very negative to very positive thing. When a person feels his/her physical condition is not the same as his/her ideal concept, the individual will feel that physical shortage even though the eyes of others already considered interesting that will eventually be many ways to achieve the ideal body image in accordance with desired. Such a condition which causes a person unable to accept his/her physical condition so that the body of his image to be low. If someone feels heavier and have excess weight, they tend to feel dissatisfied with the condition of his body and wants may lose weight. Someone who has a positive body image they perceive their bodies as something that is of interest to others. There was also someone who feels his/her body has not been ideal but already look slim or skinny but deemed not find the desired standard, so it is what can cause a person to be disturbed body image. To overcome it needed confidence that body image can be viewed and controlled with a healthy lifestyle so that the ideal self-image can be met properly. Kata Kunci: Body Image, Citra Tubuh, Perempuan.